Comparing physical activity of pedal-assist electric bikes with walking and conventional bicycles. (September 2017) - Langford, Brian Casey; Cherry, Christopher R.; Bassett, David R.; Fitzhugh, Eugene C.; Dhakal, Nirbesh
Abstract: This paper presents a study on physical activity implications of electric bikes, focusing on the users of an on-campus conventional bicycle and e-bike sharing system at the University of Tennessee. The study describes field trials of 17 users of the bikesharing system and investigates physical activity metrics on identical trips made by three different modes: walk, conventional bicycle, and pedal-assist electric bicycle. The users completed a hilly 4.43 kilometer route using each mode. Heart rate and human power output were monitored along with GPS for each bout. In addition, the study used a laboratory test to relate oxygen consumption rate (VO2 in ml/kg/min) and energy expenditure (EE kcal/kg/min) to user heart rate during bouts. Energy expenditure and ventilation rates (per minute) for all modes were not statistically different. However, total EE and VO2 for each bout (per mile) for e-bikes are 24% lower than that for conventional bicycles, and 64% lower than for walking. This reflects the shorter travel time. Differences between e-bikes and bicycles are most pronounced on the uphill segment. Still, e-bikes provide moderate physical activity (MET>3) on flat segments and downhill segments, and vigorous physical activity (MET>6) on uphill segments. For e-bike trials, riders reported higher levels of enjoyment and lower need for a shower than walk or conventional bicycle trials. This paper adds to the expanding literature by comparing e-bike, bicycle and walk EE and VO2 . E-bikes can contribute as an active transportation mode to meet required physical activity guidelines. Highlights: Compared physical activity of electric bike, conventional bicycle, and walking. Lab tests calibrate energy and ventilation rates to heart rate for trial assessment. E-bikes require less energy than regular bike (24%) and walk (64%) for same bout. E-bikes require moderate (level, downhill) and vigorous (uphill) physical activity. E-bikes elicit higher enjoyment scores, less exertion, and lower need to shower.